Progressive taxation and (in)stability in an exogenous growth model with non-market ("home") production - Aleksandar Vasilev (Journal of Economics and Econometrics, 2019)
We show that in a exogenous growth model with non-market ("home") sector calibrated to Bulgarian data under the progressive taxation regime (1993-2007), the economy exhibits equilibrium indeterminacy due to the presence of non-market production. These results are in line with the findings in Benhabib and Farmer (1994, 1996) and Farmer (1999). Also, the findings in this paper are in contrast to Guo and Lansing (1988) who argue that progressive taxation works as an automatic stabilizer. Under the flat tax regime (2008-16), the economy calibrated to Bulgarian data displays saddle-path stability. The decrease in the average effective tax rate addresses the indeterminacy issue and eliminates the "stable focus" dynamics.
Keywords: J46; D91; O41; 330; Progressive taxation; Non-market sector; Home production; Equilibrium (In)determinacy